Development Characteristics of Shale Lithofacies in the Longmaxi Formation and their Main Controlling Factors in the Changning Area, South Sichuan Basin, SW China - Tang, Qingsong; Zhou, Lu; Chen, Lei; Tan, Xiucheng; Wang, Gaoxiang (Frontiers in Earth Science, 2021)
Based on core observation, thin section, X-ray diffraction (XRD), and seismic data, the lithofacies types of organic-rich Longmaxi shale (Lower Silurian) in the Changning area of the southern Sichuan Basin were identified. The controlling factors of spatial variation in shale lithofacies and the influence of shale lithofacies on shale gas development were also analysed. Results indicate that there are mainly seven types of shale lithofacies in the Long 11 sub-member of the Longmaxi Formation, including the siliceous shale (S–1), mixed siliceous shale (S–2), carbonate-rich siliceous shale (S–3), clay-rich siliceous shale (S–4), carbonate/siliceous shale (M–1), mixed shale (M–2) and argillaceous/siliceous shale (M–4). A vertical transition from carbonate shale association + mixed shale association on the bottom, then to siliceous shale association, and mixed shale association + siliceous shale on the top generally appears in the Long 11 sub-member. The shale lithofacies of the Long 11 sub-member also laterally changes from the central depression (low-lying area) to the geomorphic highland in the east and west of the Changning area. The spatial variation of shale lithofacies in the Long 11 sub-member of the Changning area is mainly controlled by palaeogeomorphology and relative sea level. The geomorphic highland area is dominated by carbonate-rich siliceous shale and mixed siliceous shale, but the depression (low-lying area) is mainly dominated by mixed siliceous shale and argillaceous/carbonate shale.